2020
DOI: 10.3390/genes11040380
|View full text |Cite
|
Sign up to set email alerts
|

Time Series RNA-seq in Pigeonpea Revealed the Core Genes in Metabolic Pathways under Aluminum Stress

Abstract: Pigeonpea is an important economic crop in the world and is mainly distributed in tropical and subtropical regions. In order to further expand the scope of planting, one of the problems that must be solved is the impact of soil acidity on plants in these areas. Based on our previous work, we constructed a time series RNA sequencing (RNA-seq) analysis under aluminum (Al) stress in pigeonpea. Through a comparison analysis, 11,425 genes were found to be differentially expressed among all the time points. After cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Recent evidence showed that metabolic change plays an important role for cells to adapt to Al stress. Genome-wide transcriptional profiling revealed that a substantial amount of differentially expressed genes in response to Al stress are associated with metabolisms ( Fan et al, 2014 ; Xu et al, 2017 ; Gao et al, 2020 ). In rice bean ( Vigna umbellata ), Al-induced formate accumulation is responsible for Al toxicity, and VuFDH is a gene encoding formate dehydrogenase that catalyzes formate degradation, thereby conferring Al tolerance ( Lou et al, 2016a ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence showed that metabolic change plays an important role for cells to adapt to Al stress. Genome-wide transcriptional profiling revealed that a substantial amount of differentially expressed genes in response to Al stress are associated with metabolisms ( Fan et al, 2014 ; Xu et al, 2017 ; Gao et al, 2020 ). In rice bean ( Vigna umbellata ), Al-induced formate accumulation is responsible for Al toxicity, and VuFDH is a gene encoding formate dehydrogenase that catalyzes formate degradation, thereby conferring Al tolerance ( Lou et al, 2016a ).…”
Section: Introductionmentioning
confidence: 99%
“…Pigeon pea grows in tropical and subtropical regions; acidic soil is widespread in these regions. Aluminum (Al) toxicity and drought are two major constraints on plant growth in acidic soil (Ahmed et al, 2018; Gao, Dong, et al, 2020). Drought can alleviate aluminum toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Pigeon pea (Cajanus cajan, Fabaceae) is widely cultivated for its nutritional and medicinal value in tropical and subtropical regions of Asia and Africa (Gao et al 2020). Pigeon pea is the second pulse crop in India and fourth in world in terms of area, yield, and production (FAOSTAT 2018).…”
Section: Introductionmentioning
confidence: 99%